Producing microscale Ge textures via titanium nitride- and nickel-assisted chemical etching with CMOS-compatibiliyty - Liao, Yikai (2022)
As an emerging anisotropic wet etching technique, metal-assisted chemical etching (MacEtch) has been widely employed for fabricating nano- and micro-structures of germanium (Ge) for potential infrared (IR) photonics and optoelectronics. However, traditional noble metal catalysts such as Au and Ag limit its application in complementary metal oxide semiconductor (CMOS) processes, as Au is considered as a detrimental deep-level impurity in Ge. In this work, the feasibility of exploring TiN and Ni as CMOS-compatible catalysts for Ge MacEtch is investigated. Both TiN and Ni catalysts exhibit inverse MacEtch behavior, resulting in formation of inverted pyramid and v-groove Ge microscale textures which exhibit outstanding IR antireflection performance. No catalyst delamination of TiN is observed during etching, while it can be avoided by inserting a Ti adhesive layer beneath Ni catalyst. Schottky contact barrier of metal catalyst with Ge is also investigated indicating similar hole injection efficiency among TiN, Ni, and Ti/Ni with Ge junction due to strong Fermi level pinning effect. The TiN- and Ni-assisted chemical etching of Ge shed light on CMOS-compatible Ge-based photonic and optoelectronic applications.